PERAN KEPALA DESA DALAM MEMAJUKAN KESENIAN TRADISIONAL STUDI KASUS DESA BANYUSIDI, PAKIS KABUPATEN MAGELANG - Fitriasari, Rr. Paramitha Dyah (Institut Seni Indoensia Surakarta, 2010)
A leader in this regard is the head of the village is very instrumental in developing the potential existed inÂ his village. This research studies about the role of village head in promoting traditional arts, especially inÂ the village of Banyusidi, Pokis, Magelang. Central Java. The research method is qualitative withÂ multidiscipline approach. The result of this study is that the village head has u role in advancing theÂ potency of traditional arts in the village. Theï¬rst is the role of village head as a motivator, that is by givingÂ his people motivation to be able to develop the artsâ€˜ The second is village head as a facilitator providingÂ the opportunity for people to run the arts. The third is to become a patron and decision maker for hisÂ people. With those three things, then, head of the village is believed to promote traditional arts in hisÂ village.Key words: role, leader, traditional art.